Intervención de enfermería en pacientes con delirio post- sedación en la unidad de cuidados intensivos - Sani Yumisaca, Fanny Noemi (2025)
Delirium is a neuropsychiatric disorder commonly suffered by critically ill patients in intensive care units, associated with increased morbidity and mortality, frequently affecting critically ill patients. The aim of the article is to identify nursing interventions in patients with post-sedation delirium in the intensive care unit. The manuscript according to its approach was considered qualitative, because the main theoretical results on the management of delirium in post-sedation patients were analyzed, where most of the investigated data are not quantifiable and these in turn were related between articles, thus having percentages of coincidence or difference between one article and another. Among the results identified, it was presented that nursing participation is a highly multidisciplinary process, it is essential to ensure a comprehensive approach. The analgesia, sedation and delirium guidelines are an example of a strategy in which nursing should exercise care interventions taking into account the recommendations. It is concluded that nurses are essential in the early identification, prevention and control of delirium, contributing to the reduction of morbidity and mortality. Nursing interventions should be proactive and go beyond direct patient management, addressing the predisposing and precipitating factors that contribute to delirium. Identifying and managing these factors is crucial to reduce the incidence and facilitate the resolution of delirium in hospitalized patients, especially those in critical care units.